The Influence of Organizational Culture and Work Engagement Over Employee Performance Mediated by Employee Loyalty - Nadya Puspita; Natsir Nugroho; Agusdini Banun (Penerbit Kemala Indonesia, 2020)
Good employee performance is needed to achieve organizational goals and hospital success. The factors that can affect employee performance are organizational culture, work engagement, and employee loyalty. This study aims to analyze the influence of organizational culture and work engagement on employee performance with employee loyalty as an intervening variable at X Hospital, Jakarta. The design of this study is an explanatory causality study with a population of all employees at X Hospital. The sample in this study used a saturation sampling, which took all the study population as a sample, namely 68 respondents. The approach that used in this study taken by survey method that providing a questionnaire, with the measurement method using a Likert scale. The collected data were processed using descriptive and quantitative analysis tools. The testing for analyzing the data used the Path Analysis program AMOS. The results of this research showed that organizational culture has a positive and significant effect on employee performance (p=0.006), work engagement has a positive and significant effect on employee performance (p=***), and employee loyalty has a positive and significant effect on employee performance (p=***), organizational culture has a positive and significant effect on employee loyalty (p=***), and work engagement has a positive and significant effect on employee loyalty (p=***). The findings of this study indicate that organizational culture and work engagement have an effect on employee performance which is mediated by employee loyalty.